2012
DOI: 10.1128/jcm.00682-12
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Influenza B Virus with the H273Y Point Mutation in the Neuraminidase Active Site from a Human Patient

Abstract: e The H275Y oseltamivir resistance mutation confers high-level resistance to oseltamivir in isolates of human A(H1N1) influenza. We report the recovery and identification of an influenza B virus with the H273Y neuraminidase point mutation directly from a human patient. The H273Y influenza B isolate is resistant to oseltamivir and peramivir but sensitive to zanamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
3
9
0
Order By: Relevance
“…The emergence of influenza B viruses with the H274Y substi- tution was reported in a patient with no known previous antiviral treatment (69) and from surveillance studies (57 (70)(71)(72). Only by the addition of secondary permissive NA substitutions was viral fitness restored for seasonal H1N1 influenza A viruses, leading to their spread worldwide (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of influenza B viruses with the H274Y substi- tution was reported in a patient with no known previous antiviral treatment (69) and from surveillance studies (57 (70)(71)(72). Only by the addition of secondary permissive NA substitutions was viral fitness restored for seasonal H1N1 influenza A viruses, leading to their spread worldwide (73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza B viruses with these NA amino acid substitutions have been identified from patients prior to initiating antiviral treatment (23,71,72) and provide epidemiological evidence that these viruses can replicate efficiently in the absence of drug selection pressure. Importantly, oseltamivir therapy was ineffective in a 7-year-old immunocompromised patient infected with influenza B virus carrying the NA N294S amino acid substitution as virus was shed for 25 days (72).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza B viruses with reduced susceptibility to NAIs have been identified in patients before initiation of antiviral therapy and without any known exposure to the drug (Carr et al, 2011; Fujisaki et al, 2012; Hatakeyama et al, 2007; Higgins et al, 2012) (Table 1). To date, clinical studies have identified influenza B viruses carrying NA mutations either in the framework (D198N, I222T, H274Y, and N294S) (Carr et al, 2011; Hatakeyama et al, 2007; Higgins et al, 2012) or in close proximity to the enzyme active site (E105K and S250G) (Fujisaki et al, 2012; Hatakeyama et al, 2007).…”
Section: Nai Resistance Among Influenza B Virusesmentioning
confidence: 99%
“…To date, clinical studies have identified influenza B viruses carrying NA mutations either in the framework (D198N, I222T, H274Y, and N294S) (Carr et al, 2011; Hatakeyama et al, 2007; Higgins et al, 2012) or in close proximity to the enzyme active site (E105K and S250G) (Fujisaki et al, 2012; Hatakeyama et al, 2007). One common feature of these reports has been the isolation of viruses with NAI resistance-associated mutations from other close household contacts infected with influenza B and treated with antiviral drugs.…”
Section: Nai Resistance Among Influenza B Virusesmentioning
confidence: 99%
See 1 more Smart Citation